The Size Effect and Microstructure Changes of Granite after Heat Treatment - Zhongping Guo; Jian Li; Yongqi Song; Chengqian He; Fuyu Zhang (Advances in Materials Science and Engineering)
High temperature can change the mechanical properties of granite, with significant nonlinear characteristics, and at the same time change its microstructure. Therefore, two kinds of granites are used in this paper: one is normal temperature granite and the other is granite treated at 600°C, and a detailed comparative study is made. The fracture toughness of two kinds of rocks was tested by fracture tests, and the results were analyzed by a nonlinear fracture mechanics model (SEL). At the same time, in order to understand the influence of high temperature on the mineral composition and microstructure of granite, XRD, optical microscope, and SEM were used to observe the mineral composition, microcracks, and fracture morphology of granite. The results show the following: (1) high temperature significantly changes the fracture mechanics parameters of granite. The fracture toughness of granite treated at 600°C is significantly lower than that of untreated granite, which is reduced by more than 60%. (2) No obvious size effect was found in the untreated granite, while the size effect of the granite after treatment at 600°C was significant. (3) The granite after high-temperature treatment showed strong nonlinear characteristics, and the SEL can reasonably describe and explain its nonlinear fracture characteristics. (4) The brittleness of the granite treated at 600°C decreased and the ductility increased. The microscopic morphology of the fracture was rough, with obvious steps and rivers. The microcracks and porosity had increased significantly, but the main components did not change significantly.